2021
DOI: 10.31234/osf.io/pd6xh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two-year-olds’ eye movements reflect confidence in their understanding of words

Abstract: We study the fundamental issue of whether children evaluate the reliability of their language interpretation, i.e., their confidence in understanding words. In two experiments, two-year- olds (n1 = 50; n2 = 60) saw two objects and heard one of them being named; both objects were then hidden behind screens and children were asked to look towards the named object, which was eventually revealed. When children knew the label used, they showed increased post-decision persistence after a correct compared to an incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For instance, children fail to verbally identify novel objects or novel words as ones they don't know until they are about four years old (Marazita & Merriman, 2004;Slocum & Merriman, 2018). However, a recent study provides evidence that even 2-year-old children can evaluate the confidence associated with word recognition (Dautriche, Goupil, Smith, & Rabagliati, 2021), suggesting that even toddlers may be able to use basic forms of metacognition (i.e., "core" metacognition: Goupil & Kouider, 2019;Proust, 2012;Shea et al, 2014), such as the ability to estimate decision confidence, to aid in the process of learning a lexicon. Such confidence estimates could be used by children to optimise how they allocate attention during learning (e.g., ignoring situations in which high-confidence words are used), or to guide interrogative behaviors (e.g., asking clarification when confidence is low), i.e., employing active learning strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, children fail to verbally identify novel objects or novel words as ones they don't know until they are about four years old (Marazita & Merriman, 2004;Slocum & Merriman, 2018). However, a recent study provides evidence that even 2-year-old children can evaluate the confidence associated with word recognition (Dautriche, Goupil, Smith, & Rabagliati, 2021), suggesting that even toddlers may be able to use basic forms of metacognition (i.e., "core" metacognition: Goupil & Kouider, 2019;Proust, 2012;Shea et al, 2014), such as the ability to estimate decision confidence, to aid in the process of learning a lexicon. Such confidence estimates could be used by children to optimise how they allocate attention during learning (e.g., ignoring situations in which high-confidence words are used), or to guide interrogative behaviors (e.g., asking clarification when confidence is low), i.e., employing active learning strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that infants are able to evaluate the reliability of their knowledge or decisions, years before they can provide verbal reports of their knowledge states (e.g., Balcomb & Gerken, 2008;. More recently, Dautriche et al, (2021) also found that even 2-year-olds can evaluate the reliability of their lexical knowledge. In a modified version of the looking-whilelistening task (Golinkoff et al, 1987), infants looked longer towards the image they chose as the target when they had reasons to be sure about that word's meaning.…”
Section: Challenges To the Predictive Processing Approach In Language...mentioning
confidence: 99%